(untitled) (Medical Forum Monthly, 2024)
Background: The objective of Medico-legal autopsy is not only to find out the cause of death but it also helps in establishing the manner of death. It also provides information about the criminal behavior of the society and usage of different weapons. This study was carried out to find out the predominance of fire-arms weapons in homicidal deaths. Study Design: Observational study Place and Duration of Study: This study was carried out on medico legal autopsies conducted at Forensic Medicine Department K.E.M.U. Lahore during the years 2006-2008. Material & Methods: Total number of autopsies during the period was 2979. Data was extracted from autopsy reports, police papers and hospital notes. Besides the causative weapon, the cases were examined for other factors too. Like age, sex, manner of death, cause of death, seasonal variations, kind of weapon and extent of damage on the body. Results: The results clearly showed that out of these cases 1285 deaths (43.13%) were due to fire-arm weapon. Men were showing higher frequency (83%) as compared to that of female which is (17%). Homicidal cases were 61.32%, suicidal 3.8% and accidental were 7.5%. Un-determined cases were 27.5%. Homicidal incidence was highest in 3rd decade (38.58%), suicidal incidence was in 2nd decade (39.13%) and accidental incidence was high in 3rd decade of life. Homicidal/suicidal ratio was 17.1:1 and homicidal/accidental ratio was 8.1:1. Use of rifled fore-arms weapons was in 92% and smooth bored in 8.0%. In rifled fire-arms multiple entry wounds were in 52.9% cases and 47% were single entry wounds. Whereas in smooth bored single entry wounds were 66% and multiple wounds were 34%. In 56.8% homicidal deaths range of fire was distant, while it was close range in 30.4%. It was contact fire in 1.4%of suicidal cases. The blackening was seen in 16% case, tattooing in 10.58% and burning in 2.25% cases. Conclusions: There is marked predominance of homicidal deaths by fire-arms weapons and strict control over legislation will help in decreasing fire-arm fatalities.